Pengembangan potensi hutan mangrove melalui pemberdayaan masyarakat pesisir Kabupaten Teluk Bintuni: Developing the potential of mangrove forests through the empowerment of coastal communities in Teluk Bintuni Regency - Risdianto Risdianto; Hans F. Z. Peday; Andre B Arep; Ade O. Samber; Nadia Fadila; Adinda N. Putri; Marsia A. R. Rumatray; Herry Ayatanoy (IGKOJEI: Jurnal Pengabdian Masyarakat, 2026)
ABSTRACT  This community service activity aimed to empower coastal communities through the development of mangrove forest resource potential in Sarbe Village, Kuri District, Teluk Bintuni Regency, West Papua. The program was designed to improve community capacity in identifying, inventorying, and planning the sustainable utilisation of local natural resources, especially mangrove and coastal resources. The activity was carried out through observation, socialisation, interviews, surveys, technical training, and participatory inventory of village resource potential. The results showed that Sarbe Village has diverse natural resource potential with high economic value, including mangrove crabs, fish, shrimp, shellfish, mangrove wood, mangrove litter, ant nest plants, orchids, sago, sago caterpillars, game animals, handicrafts, plantation crops, fruits, and freshwater fish. These resources have long been utilised by the community for subsistence and small-scale economic activities. However, their development remains constrained by limited market access, high transportation costs, and the low capacity of local communities in value-added processing and resource management. This activity identified several priority resources that can be sustainably developed to strengthen the local economy. Continued assistance in product processing, market strengthening, and community-based resource management is needed to ensure that the development of mangrove potential contributes more effectively to the welfare of coastal communities.  Keywords: mangrove forest potential; coastal community empowerment; local resources; sustainable management; Teluk Bintuni   ABSTRAK  Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberdayakan masyarakat pesisir melalui pengembangan potensi sumber daya hutan mangrove di Kampung Sarbe, Distrik Kuri, Kabupaten Teluk Bintuni, Papua Barat. Program ini dirancang untuk meningkatkan kemampuan masyarakat dalam mengidentifikasi, menginventarisasi, dan merencanakan pemanfaatan sumber daya alam lokal, khususnya sumber daya mangrove dan kawasan pesisir, secara berkelanjutan. Kegiatan dilaksanakan melalui observasi, sosialisasi, wawancara, survei, pelatihan teknis, dan inventarisasi partisipatif terhadap potensi sumber daya kampung. Hasil kegiatan menunjukkan bahwa Kampung Sarbe memiliki potensi sumber daya alam yang beragam dan bernilai ekonomi tinggi, meliputi kepiting bakau, ikan, udang, kerang, kayu bakau, serasah bakau, tanaman sarang semut, anggrek, sagu, ulat sagu, hewan buruan, kerajinan tangan, tanaman perkebunan, buah-buahan, dan ikan air tawar. Sumber daya tersebut selama ini telah dimanfaatkan masyarakat untuk kebutuhan hidup sehari-hari maupun kegiatan ekonomi skala terbatas. Namun, pengembangannya masih dihadapkan pada kendala akses pasar, tingginya biaya transportasi, dan belum optimalnya kapasitas masyarakat dalam pengolahan hasil dan pengelolaan sumber daya. Kegiatan ini berhasil mengidentifikasi sejumlah potensi prioritas yang layak dikembangkan secara lestari untuk memperkuat ekonomi lokal. Pendampingan lanjutan dalam pengolahan hasil, penguatan pemasaran, dan pengelolaan sumber daya berbasis masyarakat masih diperlukan agar pengembangan potensi mangrove dapat lebih efektif meningkatkan kesejahteraan masyarakat pesisir. Kata kunci: potensi hutan mangrove; pemberdayaan masyarakat pesisir; sumber daya lokal; pengelolaan lestari; Teluk Bintuni